2017
DOI: 10.1016/j.jogc.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Sex Ratios at Birth Among Indian Immigrant Subgroups According to Time Spent in Canada

Abstract: Among the Punjabi and Hindi women with two previous daughters, longer duration of residence did not attenuate son-biased M:F ratios at the third birth. Gender equity promotion may focus on Punjabi- and Hindi-speaking Indian immigrant women regardless of how long they have lived in Canada.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…Similar male‐biased SRB have been observed in immigrant populations of other countries, particularly the Indian‐ and/or Chinese‐born populations of Spain, Canada, (including second‐generation mothers), Norway (although some research contradicts this), Sweden, Greece, Italy, Australia, and the United States . These trends are most evident with higher birth orders; women in these demographics with two or more girls are generally much more likely to have a boy in following pregnancies.…”
Section: Current Evidence For Sex Selectionmentioning
confidence: 54%
“…Similar male‐biased SRB have been observed in immigrant populations of other countries, particularly the Indian‐ and/or Chinese‐born populations of Spain, Canada, (including second‐generation mothers), Norway (although some research contradicts this), Sweden, Greece, Italy, Australia, and the United States . These trends are most evident with higher birth orders; women in these demographics with two or more girls are generally much more likely to have a boy in following pregnancies.…”
Section: Current Evidence For Sex Selectionmentioning
confidence: 54%
“… 22 In another study, high M/F ratios were observed to persist independently of duration of residence in Canada among Indian immigrants. 23 …”
Section: Discussionmentioning
confidence: 99%
“…Son-biased sex ratios were not found among mothers who immigrated from China to Canada. 13 However son-biased sex ratios were found among Indian immigrant mothers residing in both Canada 11 and Sweden 9 and were present after more than 10 years since arrival.…”
Section: Introductionmentioning
confidence: 99%